2021
DOI: 10.1111/1365-2435.13980
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation temporal repackaging into fewer, larger storms delayed seasonal timing of peak photosynthesis in a semi‐arid grassland

Abstract: 1. Against a backdrop of rising temperature, large portions of the western United States are experiencing fewer, larger and less frequent precipitation events.How such temporal 'repackaging' of precipitation alters the magnitude and timing of seasonal maximum gross primary productivity (GPP max ) remains unknown.Addressing this knowledge gap is critical, since changes to GPP max magnitude and timing can impact a range of ecosystem services and management decisions.2. Here we used a field-based precipitation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Because microbial respiration responds more rapidly to soil wetting than plant-mediated respiration (Carbone et al, 2011), our finding that the F s -GCC relationship is conditional on θ suggests that microbial responses to wetting dominate F s immediately after rainfall, whereas plant activity modulates F s during interstorm periods by regulating substrate availability. Prior work in this system has shown that repackaging rainfall into larger, fewer events delays peak plant productivity (Zhang et al, 2022). In this study, we observed a delayed increase in GCC for the few/large regime that was accompanied by an increase in pulse duration Frontiers in Environmental Science frontiersin.org (quantified as τ) and a decrease in pulse magnitude (Δ; Figure 6).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Because microbial respiration responds more rapidly to soil wetting than plant-mediated respiration (Carbone et al, 2011), our finding that the F s -GCC relationship is conditional on θ suggests that microbial responses to wetting dominate F s immediately after rainfall, whereas plant activity modulates F s during interstorm periods by regulating substrate availability. Prior work in this system has shown that repackaging rainfall into larger, fewer events delays peak plant productivity (Zhang et al, 2022). In this study, we observed a delayed increase in GCC for the few/large regime that was accompanied by an increase in pulse duration Frontiers in Environmental Science frontiersin.org (quantified as τ) and a decrease in pulse magnitude (Δ; Figure 6).…”
Section: Discussionmentioning
confidence: 48%
“…Thereafter, irrigation treatments were imposed with the following combinations of mean event size and dry intervals: many/small (9 mm; 3.5 days); reference (34 mm; 7 days, which is the climatic normal precipitation frequency at this site), and few/large (51 mm; 21 days). For more details about the experimental design of RainManSR, Zhang et al (2022).…”
Section: Experiments Design and Precipitation Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The semi‐arid grassland site is the Rainfall Manipulation in the Santa Rita Experimental Range experimental facility (RainManSR) near Tucson, Arizona (31.79°N, 110.90°W). The spectra used for comparison were obtained using a full spectrum ASD FieldSpec3 (Zhang et al., 2022). Measurements were pre‐season (a senescenced period during the driest June month before the monsoon), peak season (when NDVI peaks in early September), and post season (late September when NDVI has decreased to a winter minimum).…”
Section: Methodsmentioning
confidence: 99%